The effects of bluephase LED light on fibroblasts - Malčić, Ana Ivanišević; Pavičić, Ivan; Trošić, Ivančica; Simeon, Paris; Katanec, Davor; Krmek, Silvana Jukić (European Journal of Dentistry, 2012)
Objectives: The aim of this study was to evaluate the effect of Bluephase light emitting diode (LED) light on cell viability, colony-forming ability and proliferation in V79 cell culture and to determine how much the temperature of the nutrient medium rose.Methods: The investigation included a low (L), soft start (S) and high (H) illumination mode for 20, 40 and 80 seconds. The viability was determined by the trypan blue exclusion test, colony-forming ability by counting colonies 7 days after exposure and cell proliferation by the cell counts on 5 postexposure days. The temperature change during illumination was recorded (0.1˚C sensitivity).Results:In each experimental condition, 90-95% of the cells were viable, which was in the same range as the controls. Colony-forming ability was not found to be significantly lower (P<.05). A significant decrease in proliferation was recorded on the 4th post-exposure day with S and H irrespective of time, on the 3rd day with S for 80 s and H for 40 and 80 s, and with S and H for 80 s on the 2nd day (P<.05).The temperature rise was significant with S (P<.05) and H (P<.05), irrespective of exposure duration.SL=78.43%, G=66.65% and P=67.95%. Comparing the %SMHC promoted by 5 soft drinks, SL = C > CL > P = G (P<.05). There was not significant correlation between %SMHC and the other variables tested for the five drinks (P><.05)Conclusions:Dependent on total energy density, LED blue light affects the mitotic activity of cells in its path to a certain extent. Altered mitotic activity was not noted with illumination at the low power mode (intensity of 421.7 ±1.1 mW/cm2). The greatest temperature rise was 8.3 ˚C and occurred at the highest intensity and exposure duration. (Eur J Dent 2012;6:311-317)
Keywords: Tooth erosion; Carbonated beverages; Dental enamel